HUBUNGAN PAPARAN RADIASI SINAR X DENGAN KADAR HEMATOLOGI PADA PETUGAS RADIOLOGI RUMAH SAKIT PURWAKARTA: Correlation between X Ray Radiation Exposure and Hematology Level on Radiographers at Purwakarta Hospital - Novie Elvinawaty Mauliku; Ramadani Ramadani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2019)
The use of radiology in addition to providing good benefits also has a detrimentaleffect especially on workers. Radiation effects can be stochastic or non-stochastic tothe body's tissue system. The purpose of this study was to analyze X-ray radiationexposure with hematological levels in radiology officers of hospitals in Purwakartaregion. The study design was a cross sectional with the total sample population was30 respondents. Data collected using secondary data and analyzed by univariate andbivariate using the Spearman rank test. The results showed that radiation exposureof workers was 0.01mSv + 0.026 with the lowest exposure value of 0.01mSv and thehighest exposure was 0.13 mSv. There is a correlation between exposure to x-rayradiation with leukocyte levels with closeness of weak and negative patternedrelationships (p.value = 0.042; rs = - 0.146), but there is no association of x-rayradiation exposure with blood platelets, erythrocytes, eosinophils, stem neotrophilsand segments, lymphocytes and monocytes showed no relationship with very weakand negative patterns of closeness (p value> 0.05; rS <1).